STAGNASI KINERJA BPSK SEMARANG PASCA PENETAPAN UU NO. 23 TAHUN 2014 TENTANG PEMERINTAHAN DAERAH - Gunarto W Taslim (Jurnal Riptek, 2017)
Consumer protection is a human right that must be protected. The Government has the Consumer Protection Law number 8 of 1999 on Consumer Protection (UUPK) which protects consumers from various threats in transactions and in using goods and services. The law is also mandated by an institution in charge of consumer protection, namely the National Consumer Protection Agency, as well as an existing institution of local government, namely the Consumer Dispute Settlement Agency (BPSK). Since Law 23 of 2014, the local government regulates the authority to handle consumer disputes applied in the provincial government, the role of BPSK Kabupaten / Kota stagnates. January 2017 to October 2017, there is no single matter handled by BPSK Kota Semarang. This is not solely due to the absence of a budget, but BPSK Kota Semarang is afraid that if the resulting decision is considered invalid because there is no formal juridical proof that BPSK is no longer BPSK Semarang City Government but BPSK Central Java.